An overview of magnetic field exposure on germination behavior of seeds under saline stress - AMEETA SHARMA; SHEFALI SHEKHAWAT (International Journal of Pharma and Bio Sciences, 2017)
Scarcity of good quality water for irrigation as well as presence of average quality of water for use in agriculture has given rise to need for eco-friendly and safe approaches to promote plant growth and productivity. One of the most promising approaches, for future that may improve crop productivity and assures crop quality seems the use of static electromagnetic fields. In the present scenario as compared to the conventional chemical processes, magnetic field is considered as one of the simple and economic methods for enhancing and stimulation of seed germination process. The seed germination improvement have been accomplished by diverse pre-sowing seed treatments which includes a range of physical factors such as laser treatment, magnetic field and electric field application and microwave radiation. Magnetic field treatment results in accelerated growth of roots of plant as well as more proteins biosynthesis. Current research studies establish that magnetic field exposure improves seed germination parameter in various plants. Magnetic field influences germination of seeds at molecular, morphological and physiological parameters in a positive and promising way. It also helps in overcoming different types of stress especially saline. The referenced research studies provide a clear-cut explanation of the mechanism of magnetic field effect on plant seeds.